1987
DOI: 10.1007/bf02585829
|View full text |Cite
|
Sign up to set email alerts
|

Die Bedeutung der Computertomographie für Diagnostik und Therapie der Frakturen des hinteren Beckenringes und des Hüftgelenkes

Abstract: Conventional röntgenologic examinations of fifty patients with posttraumatic pelvic bone injuries were compared with computertomographic examinations. The major advantage of computertomography of the pelvis is in our view the more precise evaluation of injuries of the dorsal pelvic ring. Almost fifty percent of the fractures of the sacrum and two thirds of the injuries of the iliosacral joint in our series could not be diagnosed on conventional examinations. Computertomography of fractures of the sacrum and fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

1994
1994
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 5 publications
0
5
0
1
Order By: Relevance
“…The real extent of the pelvic injury is then underestimated. With a pelvic CT, fractures and dislocations of the posterior pelvis can be analyzed in more detail [ 5 ]. Consequently, a pelvic CT is indispensable for complete evaluation of an FFP.…”
Section: Introductionmentioning
confidence: 99%
“…The real extent of the pelvic injury is then underestimated. With a pelvic CT, fractures and dislocations of the posterior pelvis can be analyzed in more detail [ 5 ]. Consequently, a pelvic CT is indispensable for complete evaluation of an FFP.…”
Section: Introductionmentioning
confidence: 99%
“…In previous studies conventional radiography has been found to be inferior to CT (1)(2)(3)(4)(5)(6)9,II,(13)(14)(15)(16)(17). Especially abnormalities of the posterior pelvic ring, the extent of acetabular fractures and the presence of intraarticular hip fragments were often missed by analyses of conventional radiographs.…”
Section: Discussionmentioning
confidence: 96%
“…Conventional radiography is usually the most rapidly available modality, but often an additional CT examination is warranted. Many reports have been published comparing these 2 methods (1)(2)(3)(4)(5)9,(13)(14)(15)(16)(17), but no investigation has compared the ability of these 2 methods to classify the injuries and identify fractures in each individual part of the pelvis. We therefore designed a blind study to compare the findings by conventional radiography and CT in order to determine when CT provides additional information, and which lesions are best evaluated by CT and which by conventional radiography.…”
mentioning
confidence: 99%
“…Da Hüftpfannenbrüche nur in einigen wenigen Ausnahmefällen primär operativ versorgt werden, wird die Entscheidung auf der Basis suffizienter radiologischer und fallweiser CT-Untersuchungen nicht unter Zeitdruck fallen müssen und dadurch erleichtert [2,3,6,12,16,17,21].…”
Section: Schlüsselwörterunclassified